2008
DOI: 10.1111/j.1468-3083.2008.02612.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium level in Iranian patients with alopecia areata

Abstract: because of the potential risk for occult regional lymph node metastases. This technique, widely used in the nodal staging of malignant melanoma and breast carcinoma, has been effectively employed also to detect occult nodal metastases in patients with high-risk non-melanoma skin cancers. 10 It can select patients for radical lymphadenectomy, sparing unnecessary nodal dissection, when SLN lacks of metastasis.Subsequent experiences are essential to support our options in the management of malignant PTT. R Cecchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Magnesium acts as a cofactor for over 300 enzyme systems, and plays an important role in nucleotide synthesis, a frequent process in the rapidly dividing hair follicle [64]. A small number of studies have investigated the serum levels of these elements in AA (Table 3) [54–58, 65] and few have identified an association between low levels and AA. In one study [56] of 27 AA patients from Iran, serum and hair copper levels were lower in AA patients compared to controls.…”
Section: Micronutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium acts as a cofactor for over 300 enzyme systems, and plays an important role in nucleotide synthesis, a frequent process in the rapidly dividing hair follicle [64]. A small number of studies have investigated the serum levels of these elements in AA (Table 3) [54–58, 65] and few have identified an association between low levels and AA. In one study [56] of 27 AA patients from Iran, serum and hair copper levels were lower in AA patients compared to controls.…”
Section: Micronutrientsmentioning
confidence: 99%
“…Regarding selenium, two studies have yielded conflicting results. In an Iranian study [65], 29 patients had lower selenium levels compared to controls, while a Finish study found no differences between AA cases and controls [58]. …”
Section: Micronutrientsmentioning
confidence: 99%
“…The primary indicator of iron status relied upon in hair loss studies is serum ferritin. Serum levels of this iron-binding protein reflect a patient's total iron storage [8].Therefore, this study aimed to investigate the role of zinc and ferritin in patients with alopecia areata…”
Section: Introductionmentioning
confidence: 99%
“…An Iranian study has compared patients with several degrees of alopecia areata to a control group and observed significantly lower serum selenium levels in the first group though there was no statistical difference among cases. [ 5 ] In our own records, 40 patients with alopecia areata were evaluated with serum selenium dosage, and there was no statistically significant difference between them and a control group.…”
mentioning
confidence: 99%